Preparation and investigation of unnatural polar sidechains in designed coiled-coils - Diss, Maria L., author; Kennan, Alan, advisor (Colorado State University. Libraries, 2008)
Programmed self-assembly of discrete molecular species to form complex aggregates provides the opportunity to both refine and exploit current knowledge of molecular recognition patterns. Self-assembly events dominate the precise control and understanding of macromolecular structure, placing a premium on development and discovery of molecular recognition motifs. One such motif is the alpha helical coiled coil. A key natural strategy for controlling specific assembly is the burial of polar side chains (particularly asparagines) at central hydrophobic core positions. Alignment of the polar side chains opposite each other, rather than opposite hydrophobic alternatives, drives formation of the intended complex. Utilizing this polar contact, we sought to control coiled-coil formation through the use of unnatural polar side chains. These unnatural side chains included various chain length arginine derivatives and the corresponding urea analog, citrulline, along with its chain length variants. Synthetic methodology compatible with solid phase peptide synthesis was developed to form the desired functionalized primary amine side chain. Guanidinylation occurred in one step through the use of a di-2-Cl-Z protected pyrazole derivative. Urea formation also proceeded in one step through the use of a preformed p-methoxybenzyl-p-nitrophenyl carbamate. Deprotection to give the desired functional group occurred through standard cleavage conditions. With the establishment of the synthetic methodology, numerous peptides were synthesized incorporating these new polar groups into the hydrophobic core. Additionally, asparagine, aspartic acid, and glutamic acid were used as core residues. Heterodimeric mixtures of these sequences with guanidine, urea, amide and carboxylic acid binding partners form a large number of reasonably stable coiled coils (Tm ≥ 60 °C), allowing for application-specific tuning. A number of four-component selective recognition systems are also presented, in which two distinct heterodimers form from an input of four different peptides. More impressively, examples of six-component systems are demonstrated. Control mixtures establish subtle structural requirements for successful recognition. Having demonstrated successful recognition motifs within a dimeric system, a trimeric system has been investigated. Once again, these polar contacts allow for heterotrimerization. However, the relatively narrow stability range of these trimers does not allow for successful exchange experiments (Tm = 43 to 59 °C).
Keywords: coiled coils; guanidine; polar sidechains; biochemistry; organic chemistry